Peran Pendidik dalam Meningkatkan Manajemen Sekolah pada Masa Pandemi - Setiawan, Farid; Riyadi, Dias Syahrul; Ledia, Shinta; Duandanto, Yayan Bagus (Lembaga Yasin AlSys, 2021)
The purpose of this study is to find out how the role of educators in improving school management is and what challenges educators can face in school management. This is so that the author as a prospective teacher can find out what role he should have when he becomes a teacher. In this article, in obtaining data the author uses a descriptive qualitative research method. Because the data in this paper describes the importance of the role of educators in improving school management during the pandemic. Poor management will affect the development of schools, especially during a pandemic like today. The factor that influences the management is the backwardness of science and technology brought about by the current of globalization which results in a school having a quality performance that lacks direction, planning, and good conditioning and organization. As is happening in Indonesia today, which is experiencing problems in the world of education during the COVID-19 pandemic. In developing schools, school management is needed which will later support success in achieving the goals that have been set, but in its development it must pay attention to the principles of school management which consist of four principles, namely Equifinality, Decentralization, Self-Management System and Human Initiative.